Implementasi Program Literasi Membaca 15 Menit Sebelum Belajar Sebagai Upaya Dalam Meningkatkan Minat Membaca - R. Anisya Dwi Septiani; Widjojoko; Deni Wardhana (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
The Condition of schools in Indonesia, there are several schools that have not created a literate school atmosphere both physically, socially, and learning. This requires challenges and strategies so that these illiterate schools become literate schools and become literate schools that are entrenched in school. This is driven by observations carried out at SDN Wanajaya 03 showing an indication of the low interest in reading the students show that during the teaching and learning process related to reading students are not enthusiastic, the means to support reading activities are not available due to the absence of library facilities and from the result of interviews shows that from 23,9% agree and as much 70,5% strongly agree to visit a library that is more complete than the library in school, this research is a field research with a qualitative research approach, for data collection techniques are carried out by observation, interview, and documentation, data analysis using data reduction, data presentation, and drawing conclusion. The purpose of this study is to a provide a description of the implementation of the reading literacy program 15 minute before learning, this program is carried out in three stages: the first stage is the habituation stage where this stage has started to be carried out and is able arouse students motivation and can distinguish the types of reading book, the stage that the second is the development stage where students do not just read but better understand what is read and are able to write the story into everyday life, the third stage is the learning stage where at this stage literacy activities can be carried out independently without any coercion or coercion. Order this literacy activity is linked to other learning. The role of teachers and parents is very important for the running of this literacy program.